SPACES OF ATHENSIC CONNECTION ON THE TANGENTIALLY DEGENIED SURFACE OF A REGULAR HYPERPOLOS OF NON-Euclidean SPACE - Гребенюк, М. Ф. (Proceedings of National Aviation University (archive), 2021)
Regular hyperbands of metrized projective space with absolute are considered. Geometric objects are introduced, which determine the invariant equipment of the hyperband in the sense of AP Norden in the vicinity of the third order. A pair of spaces of dual affine geesities associated with the tangentially degenerate surface of a given hyperband is constructed.